How do you solve using gaussian elimination or gauss-jordan elimination, 3x – y + 2z = 6, -x + y = 2, x – 2z = -5?

1 Answer
Jul 16, 2016

color(red)(x=1,y=3,z=3)

Explanation:

Initial Augmented Matrix:

[ ( 3, -1, 2, 6), ( -1, 1, 0, 2), ( 1, 0, -2, -5) ]

Adding Row-2 and Row-3 to Row-1

[ ( 3, 0, 0, 3), ( -1, 1, 0, 2), ( 1, 0, -2, -5) ]

Dividing Row-1 by 3

[ ( 1, 0, 0, 1), ( -1, 1, 0, 2), ( 1, 0, -2, -5) ]

Adding Row-1 to Row-2

[ ( 1, 0, 0, 1), ( 0, 1, 0, 3), ( 1, 0, -2, -5) ]

Adding Row-1 from Row-3

[ ( 1, 0, 0, 1), ( 0, 1, 0, 3), ( 0, 0, -2, -6) ]

Dividing Row-3 by -2

[ ( 1, 0, 0, 1), ( 0, 1, 0, 3), ( 0, 0, 1, 3) ]

Obviously

color(red)(x=1,y=3,z=3)